Iqbal and sufism (Part Five) - Abdul Razak, Mohd Abbas (Islam on Web (The Window to Islam), 2023)
Besides his criticism of the West, Iqbal felt disturbed to witness the development that was taking place in the Muslim world. It saddened him to see the mushrooming of a kind of Sufism which preached to the masses to indulge zealously in all spiritual practices, and at the same time, either neglect or pay little interest in calling people to perform their worldly duties actively as mentioned in the Qur’an. It was clear to Iqbal that such a message was contrary to what the Muslims have been told to do in carrying out their duty as Allah’s vicegerent.